Odpowiedzialność posiłkowa w prawie karnym skarbowym — uwagi co do zasadności jej stosowania - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article is devoted to the institution of. It is an independent institution in fiscal penal law. Auxiliary liability raises a lot of doubts. They concern imposing a fine for the fiscal offence on a person other than the person who committed it. The additional person is not guilty of an offence, but still pays a fine according to the Fiscal Penal Code. Because in the doctrine a civil law character is assigned to auxiliary responsibility, the author suggests abolishing this institution in fiscal penal law. The article presents the arguments in favour of it. Above all, the author demonstrates the contradiction with the principle of guilt applicable in criminal law.
Keywords: odpowiedzialność posiłkowa; prawo karne skarbowe